2015
DOI: 10.1088/0741-3335/58/2/025001
|View full text |Cite
|
Sign up to set email alerts
|

Research on the effect of resonant magnetic perturbations on disruption limit in J-TEXT tokamak

Abstract: The effect of resonant magnetic perturbations (RMPs) on high density limit and low-q limit discharges is studied in J-TEXT tokamak. It is found that a moderate amplitude of applied RMPs increases the density limit and delays the disruption, and the disruption precursor is suppressed with a slight reduction in toroidal plasma rotation. A too large amplitude of RMPs, however, leads to a lower density limit and an earlier disruption. For the optimal RMPs amplitude, the disruption is delayed by about 150 ms. For l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 31 publications
(51 reference statements)
0
14
0
Order By: Relevance
“…However, most of the experimental and modeling results have focused on stable and healthy plasma, which is obviously different for the actual situation in ITER. For the inevitable disruption in ITER, uncontrolled modes, which can be controlled for instance by a combination of applied resonant magnetic perturbation (RMP) [19][20][21], electron cyclotron current drive [22] and electrode biasing [23], are likely to appear before the application of DMS [24]. In addition, statistical studies of disruptions on JET have found that they nearly all exhibit signs of mode locking before the disruption takes place [25].…”
Section: Nuclear Fusionmentioning
confidence: 99%
“…However, most of the experimental and modeling results have focused on stable and healthy plasma, which is obviously different for the actual situation in ITER. For the inevitable disruption in ITER, uncontrolled modes, which can be controlled for instance by a combination of applied resonant magnetic perturbation (RMP) [19][20][21], electron cyclotron current drive [22] and electrode biasing [23], are likely to appear before the application of DMS [24]. In addition, statistical studies of disruptions on JET have found that they nearly all exhibit signs of mode locking before the disruption takes place [25].…”
Section: Nuclear Fusionmentioning
confidence: 99%
“…Previous researches on J-TEXT demonstrated that the field penetration threshold increases with the increase of density and scales proportionally to n 0.5 e in the range of (0.7-2.7) × 10 19 m −3 [20]. However, an unexpected lower field penetration threshold was recently observed in higher density plasma in a series of discharges [30]. Facts above show that the field penetration threshold can even decrease with an increase of the density in some cases, accentuating the question how the field penetration threshold depends on the density.…”
mentioning
confidence: 94%
“…Theories of error field penetration have been developed in past decades and explained the experimental observations [6,[17][18][19][20][21]. In particular, for locked mode theory based on the frame of MHD [22][23][24][25], the bifurcated state of rotating plasma has been analyzed in different response regimes.…”
Section: Introductionmentioning
confidence: 99%